The Effect of Trust and Related Party Transaction on Firm Value - Ramadhani, Raihan; Diantimala, Yossi; Arfan, Muhammad (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 2 (2022), 2022)
This study investigates the impact of trust and related party transactions on the valuation of firms, focusing on 185 banking companies listed on the Indonesia Stock Exchange over the period 2016-2020. Employing multivariate analysis to test the hypothesis, the findings reveal that both trust and related party transactions significantly enhance firm value. This suggests that the inclusion of the term 'trust' in the Management Discussion and Analysis (MD&A) report is indicative of a company's commitment to ethical governance and effective management, which in turn boosts investor confidence. Additionally, an increase in debt transactions with related parties facilitates easier access to funding for operational activities and investment expansion compared to the complexities involved in securing loans from external third parties. Keywords : trust, related party transactions, firm value, MD&A